TECHNICAL SAFETY IN GREENHOUSES - Orinova Sadokatoy Kobuljonovna; Sunnatulla Sulaimonov (European Science Publishing, 2024)
Working in greenhouses plays a key role in agriculture in ensuring the cultivation of various crops throughout the year. However, like any other field of activity, working in greenhouses involves certain risks for the health and safety of workers. The problem of ensuring labor protection and safety in greenhouses is becoming urgent, especially in connection with the growing demand for organic products and the expansion of the scale of production. Despite the apparent safety, work in greenhouses is fraught with many potential risks, from mechanical injuries to occupational diseases, and information on countermeasures was provided.
Keywords: greenhouse, workers, conditions, assessment of working conditions, improvement, negative factors, risk, production environment.